1968
DOI: 10.1901/jaba.1968.1-253
|View full text |Cite
|
Sign up to set email alerts
|

THE ROLE OF SOCIAL AND MATERIAL REINFORCERS IN INCREASING TALKING OF A DISADVANTAGED PRESCHOOL CHILD1

Abstract: Adult social reinforcement and access to materials in the preschool were made contingent on the verbalizations of a 4-yr-old Negro girl with an extremely low frequency of talking. Though the teachers' social attention was always given immediately for all spontaneous speech, if the child's spontaneous verbalizations were requests for materials, those materials were withheld until she had responded to the teachers' questions about those materials. When she was silent, the teachers withheld their attention and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0

Year Published

1970
1970
1987
1987

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 8 publications
2
35
0
Order By: Relevance
“…A similar study of a 3-yr-old isolate boy reported by Harris, Wolf, and Baer (1964) indicated that by changing the contingencies for adult attention, rapid changes in social behavior of the child resulted. Reynolds and Risley (1968) demonstrated that material as well as social reinforcers could be used to modify social behavior in the nursery. Buell, Stoddard, Harris, and Baer (1968) The present experiment attempted to increase the rate of interaction between an isolate boy and his nursery school classmates.…”
mentioning
confidence: 99%
“…A similar study of a 3-yr-old isolate boy reported by Harris, Wolf, and Baer (1964) indicated that by changing the contingencies for adult attention, rapid changes in social behavior of the child resulted. Reynolds and Risley (1968) demonstrated that material as well as social reinforcers could be used to modify social behavior in the nursery. Buell, Stoddard, Harris, and Baer (1968) The present experiment attempted to increase the rate of interaction between an isolate boy and his nursery school classmates.…”
mentioning
confidence: 99%
“…Reynolds and Risley (1968) and Hart and Risley (1968) collected verbal samples by instructing observers to follow a child from one activity to another and write down in longhand "everything" the child said. Reliability checks taken periodically over the year yielded very acceptable product-moment correlation coefficients between observers in both cases.…”
Section: The University Of Tennesseementioning
confidence: 99%
“…Promptly, however, some researchers began examining the effect of another class of more-natural reinforcers-play activities and materials, and free time. These "natural" reinforcers were found in the home (Nordquist and Wahler, 1973;Phillips, 1968), in psychiatric institutions (Ayllon and Azrin, 1968;Mitchell and Stoffelmayr, 1973), and in educational settings for children and adolescents.6 It has been argued that natural reinforcers should be used whenever 6Betancourt and Zeiler, 1971;Brigham et al, 1972;Harris and Sherman, 1973;Hopkins et al, 1971;Jacobson et al, 1969;Knapczyk and Livingston, 1973;Miller and Schneider, 1970;Osborne, 1969;Reynolds and Risley, 1968;Salzberg et al, 1971;Wolf et al, 1968. possible because they should facilitate generalization of behavior change (Axelrod, 1971;Lovaas, Koegel, Simmons, and Long, 1973).…”
mentioning
confidence: 99%